Behavioural finance perspectives on Malaysian stock market efficiency - Tuyon, Jasman; Ahmad, Zamri (Elsevier, 2016)
This paper provides historical, theoretical, and empirical syntheses in understanding the rationality of investors, stock prices, and stock market efficiency behaviour in the theoretical lenses of behavioural finance paradigm. The inquiry is guided by multidisciplinary behaviouralrelated theories. The analyses employed a long span of Bursa Malaysia stock market data from 1977 to 2014 along the different phases of economic development and market states. The tests confirmed the presence of asymmetric dynamic behaviour of prices predictability as well as risk and return relationships across different market states, risk states and quantiles data segments. The efficiency tests show trends of an adaptive pattern of weak market efficiency across various economic phases and market states. Collectively, these evidences lend support to boundedadaptive rational of investors' behaviour, dynamic stock price behaviour, and accordingly forming bounded-adaptive market efficiency.